Tutelas de urgências no processo arbitral - Nunes, Soraya Vieira (2013)
This dissertative paper proposes the analysis of the appreciation of the guardianships of urgency in seat of the arbitration, in the preceding and incidental phases. With this goal, the paper seeks to study the competence of the arbitrator to decide the precautionary and anticipatory measures, before and after the installation of the arbitral proceedings, in light of the Arbitration Act, of the current Civil Procedure Code, of the regulations from the Arbitration Chambers, of the result of the research undertaken between the Law School of São Paulo from the Getúlio Vargas Fundation and the Brazilian Arbitration Committee, of the doctrine, the jurisprudence and of the Reform Project of the Civil Procedure Code. Although divergent interpretations were identified in the doctrine about the power of the arbitrator to grant and judge the emergency measures, due to the prevision of Article 22, § 4 of Law No. 9.307/96, there is the prevailing understanding that the arbitrator holds the referred power against the autonomy of the parties. Regarding the pre-arbitration precautionaries, the judiciary is vested with the power of decision, while not initiated the arbitration proceedings, except when the parties impute the arbitrator with the decision, through the prevision in the Arbitral Convention or in the Arbitration Rules of the Chamber chosen by them to administer the arbitration. It is evident in the doctrine, as well as in the jurisprudence, the understanding about the sovereignty of the arbitrator to keep or reject judicially the precautionary measures considered, in seat of the arbitration award. Due to the absence of coercive power of the arbitrator, it is identified the cooperation of the judiciary to comply with precautionary and anticipatory arbitration awards, not met voluntarily by the parties, to ensure the effectiveness of the jurisdictional protection.